Brand Management of Catholic Church in Poland - Grzegorz Ignatowski; Łukasz Sułkowski; Robert Seliga (Religions, 2020)
Building the brand of the Catholic Church is an area that is little explored in the literature on the subject. This issue turns out to be a very controversial area due to the nature of the activities and the sphere in which these activities are to be performed (marketing, ethics, religion, and faith). The article presents the results of qualitative research conducted among clergymen in Poland and is additionally based on the analysis of the literature on the subject. The theoretical considerations and research results presented in the article help to develop an understanding of the activities of the Catholic Church in Poland, aimed at strengthening the value of its brand. It should be noted that the generational change taking place in Poland forces the clergy to change their narrative and way of conducting dialogue. The previous generations, based on the faith and ethos of John Paul II, also expect modern forms of communication more and more often, which leads to building the brand value of the Catholic Church in Poland. The article discusses the specificity of the interdependence of the Church and marketing, identifies the issues of building the brand of the Catholic Church and the use of modern marketing tools in this process, and presents the results of its own research, which leads to the drawing of final conclusions verifying the research questions posed in the research methodology. This article may initiate an extended discussion on the controversial topic of the implementation of commercial marketing tools into management processes in the Catholic Church.